Implementasi Nilai-Nilai Pendidikan Multikultural di Perguruan Tinggi (Studi Kasus di Prodi PGSD Universitas PGRI Palembang Sumatera Selatan) - Miftahul Husni (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The Republic of Indonesia is a country that has a very heterogeneous and pluralistic population, starting from religion, ethnicity, culture and also language. So the motto of this country is "Binneka Tunggal Ika" which means different but still one. So of course to be a safe and peaceful country must respect and respect differences. But a few years ago, togetherness and mutual respect for differences began to be shaken by the emergence of identity politics, with the emergence of identity politics resulting in the formation of two major groups, namely the moslem group which became the largest population and also non-Islamic groups, between the two groups occurring extraordinary friction, plus irresponsible elements of the two groups become scissors that always damage and disintegrate the community through posting on their respective social media, in addition to that hoaks information also has a negative impact on the poor attitude of the Indonesian people's tolerance . then with these welds researchers want to see how the values of multicultural education are implemented in the university area. The focus of the problem in this research are, 1. How are the principles of planting multicultural education values at PGRI University in Palembang ?, 2. How about planting multicultural education values at PGRI Palembang University?, 3. What are the implications of planting educational values multicultural toward the tolerance attitude of Palembang PGRI University students?. This type of research is a qualitative descriptive research, using observational data collection, interviews and documentation. The data analysis technique is triangulation (data reduction, data display, and drawing conclusions). The results of the study explained that there are three principles of multicultural education values at PGRI university, including the principles of democracy, equality and justice, these three principles are the foundation for the application of multicultural education values at PGRI University, then the implementation of educational values multiculturalism is carried out through formal and non-formal education, in addition to that campus services also highly uphold multicultural values